RELATIONSHIP LONG SITTING, SITTING POSITION, AND STUDENT STATUS WITH LOW BACK PAIN COMPLAINTS IN STUDENTS OF IBNU SINA UNIVERSITY, BATAM CITY IN 2023 - Wijaya, Juhanda Kartika; Sari, Novrika; Oktarizal, Hengky (Jurnal Ilmu Kesehatan, 2023)
Low Back Pain or lower back pain is an injury that is found as a result of poor physical activity. One of the factors that can influence the occurrence of complaints of low back pain is position, duration of sitting, and during activities. This study aimed to determine the relationship between sitting duration, sitting position, and student status with complaints of low back pain in college students. A cross-sectional analytic survey study was carried out on 107 people using a questionnaire, sampling was taken by random sampling. Questionnaire results were tested by Chi-Square statistical test. It was found that there was a relationship between long sitting and complaints of low back pain in Ibnu Sina University students with a p-value of 0.05; r 2 = 0.04. There is a relationship between sitting position and complaints of low back pain in Ibnu Sina University students, p-value 0.05; r 2 = 0.02. There is a relationship between student status and complaints of low back pain in students at Ibnu Cyan University, p-value 0.05; r 2 = 0.03. This study concludes that there is a relationship between sitting time, sitting position, and student status with complaints of low back pain among students at Ibnu Sina University, Batam City in 2023